When dysbiosis meets dystrophy: an unwanted gut-muscle connection - Anusha, Jayaraman; Pettersson, Sven * (Springer, 2023)
Duchenne muscular dystrophy (DMD) is a devastating neuromuscular degenerative disease with no known cure to date. In recent years, the hypothesis of a "gut-muscle axis" has emerged suggesting that bidirectional communication between the gut microbiota and the muscular system regulates the muscular function and may be perturbed in several muscular disorders. In addition, the excessive consumption of sugar and of lipid-rich processed food products are factors that further aggravate the phenotype for such diseases and accelerate biological aging. However, these unhealthy microbiota profiles can be reversed by individualized dietary changes to not only alter the microbiota composition but also to reset the production of microbial metabolites known to trigger beneficial effects typically associated with prolonged health span. Two recent studies (in this issue of EMBO Mol Med) highlight the interesting potential of microbiota-informed next-generation dietary intervention programs to be considered in genetically linked muscle disorders like DMD.